Relationship Between Work Experience And The Ability To Perform Nursing Actions In The Inpatient Ward Of Mukomuko Regional General Hospital - Kadir, Sultan A; Darmawansyah, Darmawansyah; Hermiati, Dilfera (Utami Publisher, 2025)
The ability to perform good nursing practices is very important in health care services. Work experience is a factor that is thought to influence nurses' abilities. This study aims to determine the relationship between work experience and nurses' ability to perform nursing practices in the inpatient ward of Mukomuko Regional General Hospital. The study design is observational with a cross-sectional approach, involving 36 nurses using total sampling technique. Data were collected using a work experience questionnaire and a nursing competency observation sheet. The results showed that most nurses had high work experience (61.1%) and high nursing competency (58.3%). The chi-square test showed a significant relationship between work experience and the ability to perform nursing actions (p=0.001). Conclusion: There is a significant relationship between work experience and nurses' ability to perform nursing actions. It is recommended that Mukomuko Regional General Hospital improve coaching and training to strengthen nurses' competencies.